Miscellanea umanistica, silloge epigrafica, libro di famiglia, cronaca: il corpo fluido del ms. G 47 della Biblioteca Vallicelliana di Roma - Caldelli, Elisabetta (Scrineum, 2024)
This essay aims to describe and analyse in detail the ms. G 47 of the Biblioteca Vallicelliana in Rome, a codex from the second half of the 15th century, known mainly as an epigraphic collection, but actually with a much richer and more complex structure, a long life and a nature that is not easy to place within the late medieval manuscript production.